Social planning and local welfare. The experience of the Italian area social plan. Issue 2 (3rd April 2019) - Previtali, Pietro; Salvati, Eugenio
ABSTRACT: This article analyses the Italian experience of planning and governance in local welfare systems, after the adoption of a specific planning instrument called the 'Piano di Zona' (Area Social Plan), which has reached its sixth triennial review. Our goal is to explore the relationship between governance and performance by examining under which circumstances the social planning is successful, that is one Area Social Plan is preferable to another. Our research is based on the empirical observation of the nine Area Social Plans in the Province of Pavia which involves 188 municipalities. Our results demonstrate the fundamental role of public administrations and the negative effects that horizontal multi-level forms of governance may have on the planning of the Area Social Plan, almost as though there were a sort of path dependence from previous/pre-existing governance relationships.